Compressive mechanical properties of cottonseed - Zheng, Yuanzhao; Wang, Meng; Du, Xintian; Zhang, Hongwen; Wang, Lei; Wei, Ximei; Fu, Xuewen; Wang, Jun (Frontiers in Materials, 2023)
Understanding cottonseeds' basic physical parameters and compressive mechanical properties is necessary in seed cotton packing and cottonseed processing. In this study, the basic physical parameters of three cottonseed varieties (Huiyuan 720, Xinluzao 61 and Xinluzao 74) under different moisture contents (6%, 9%, 12% and 15%) were measured. These parameters include 1000-grain weight, triaxial dimension and sphericity. The effects of different moisture, varieties and compression orientation (horizontal and vertical) on the compressive mechanical properties of the cottonseed were studied and the variance analysis of the experimental data showed that the triaxial dimension, 1000grain weight, arithmetic mean diameter and geometric mean diameter of cottonseeds of the same variety increased with increase in moisture content. Extremely significant differences (P<0.01) were found in the physical parameters amongst different varieties. The main factors affecting crushing force and apparent elastic modulus are moisture content, variety and compression orientation. For deformation, the main factors are moisture content, compression orientation and variety. Moreover, compression orientation, moisture content and variety are the main factors affecting failure energy. The results obtained that the crushing force and apparent elastic modulus decreased, deformation increased, and failure energy decreased first and then increased with the increase of moisture content under the same cottonseed variety. The results also provided the basic physical parameters for the design parameter optimization of seed cotton harvesting and processing machinery.